Hubungan Keterpaparan Asap Rokok Dengan Kejadian Hipertensi Di Puskesmas Alai Kota Padang Tahun 2023 - Daeng Ramadhan salim (Jurnal Amanah Kesehatan, 2023)
The prevalence of hypertension in West Sumatra is around 22.6%, in Padang City in 2021 it will be 51.36%. Based on 2023 Community Health Center data, the incidence of hypertension at Alai Community Health Center is the 3rd largest out of 23 community health centers in Padang City with a figure of 63.1%. Hypertension is the second highest disease after ISPA which is often treated at the Alai Community Health Center. The aim of this research is to determine the relationship between exposure to cigarette smoke and the incidence of hypertension at the Alai Health Center in Padang City. This type of quantitative research uses a descriptive analytical method with a cross sectional study approach. This research was conducted in March-August 2023 at the Alai Health Center, Padang City. The population was 309 people, a sample of 57 people using a purposive sampling technique. The results showed that almost half of the 24 (42.1%) patients experienced moderate hypertension and more than half of the 42 (73.7%) patients were exposed to cigarette smoke. There was a significant relationship between hypertension and exposure to cigarette smoke at the Alai Community Health Center, Padang City (p=0.000). Based on the research results, it can be concluded that cigarette smoke has an effect on increasing blood pressure. It is recommended for active smokers to reduce their smoking habits at home and away from the reach of other family members in order to minimize the risk of exposure to cigarette smoke which causes hypertension. the reach of other family members in order to minimize the risk of exposure to cigarette smoke which causes hypertension. Keywords:hypertension; exposure to cigarette smoke